ANALISIS STRATEGI PEMASARAN DAN PENGEMBANGAN PASAR SEGAR STREET FOOD DI KABUPATEN PINRANG - MUHAMMAD WAHYUDDIN; MUSTARI; MUHAMMAD DINAR; NURDIANA; MUH. IHSAN SAID (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The purpose of this study is to look at different marketing strategies and market development opportunities in the food industry. This research is a qualitative descriptive study. Data was collected through observation, interviews, and documents. Internal Evolutionary Factor (IFE), External Evolutionary Factor (EFE), Internal Evolutionary Factor (IE), Strengths, Weaknesses, Opportunities, and Threats (SWOT), and Strategic Planning Matrix are all examples of internal evolutionary factors. The analysis technique includes quantitative strategy (QSPM). The findings show that the strategy that can be applied to the culinary area is one of maintenance and maintenance. According to the SWOT matrix, the food sector can use nine marketing strategies. According to the QSPM results from nine strategies, maintaining prices and improving product quality to increase customer satisfaction and loyalty is one of the preferred strategies with a TAS score of 4,766.